Effect of Pd/ZnO Morphology on Surface Acoustic Wave Sensor Response - Dana Miu; Izabela Constantinoiu; Cornelia Enache; Cristian Viespe (Nanomaterials, 2021)
Laser deposition was used to obtain Pd/ZnO bilayers, which were used as sensing layers in surface acoustic wave (SAW) sensors. The effect of laser deposition parameters such as deposition pressure, laser energy per pulse, laser wavelength or pulse duration on the porosity of the Pd and ZnO films used in the sensors was studied. The effect of the morphology of the Pd and ZnO components on the sensor response to hydrogen was assessed. Deposition conditions producing more porous films lead to a larger sensor response. The morphology of the ZnO component of the bilayer is decisive and has an influence on the sensor properties in the same order of magnitude as the use of a bilayer instead of a single Pd or ZnO layer. The effect of the Pd film morphology is considerably smaller than that of ZnO, probably due to its smaller thickness. This has implications in other bilayer material combinations used in such sensors and for other types of analytes.